Evaluation of the cultivar mixture strategy as a sustainable tool for managing weeds and enhancing rice yield - Jareen, Bushra; Anwar, Md Parvez; Anwar, Sabina Yeasmin; Mominul Islam, A. K. M.; Rashid, Md Harun Or; Sultana, Most Tamanna Sultana,; Juraimi, Abdul Shukor (Zibeline International Publishing, 2019)
The study was conducted to evaluate the potentiality of rice cultivar mixtures as a strategy for managing weeds and increasing the rice yield under different weeding regimes. Two rice cultivars having different plant stature and maturity periods viz. Binadhan-13 and BRRI dhan56 were used in this study. Factors included six cultivar mixture ratios viz. sole Binadhan-13, sole BRRI dhan56, 2:3, 3:2, 2:4 and 4:2 Binadhan-13 to BRRI dhan56, and four weed management practices viz. no, one, two and three weeding. The experimental design was randomized complete block with three replicates. Both the cultivars showed better growth, higher weed suppression and increased yield when grown in mixture irrespective of ratios compared to their monoculture performances. Based on the total rice grain yield, different mixture ratios performed in the order 4:2, 3:2, 2:3 and 2:4 Binadhan-13 to BRRI dhan56. Binadhan-13 and BRRI dhan56 inter-planted in 4:2 row ratio appeared as the best mixture ratio which resulted in 136% and 7% yield advantages and 17% and 24% weed dry matter reduction over sole culture of Binadhan-13 and BRRI dhan56, respectively. Hence, cultivar mixture strategy can be adopted as an effective tool for better weed management and increased yield of rice.